Digital microscopy as valid alternative to conventional microscopy for histological evaluation of Barrett's esophagus biopsies - van der Wel, M J; Duits, L C; Seldenrijk, C A; Offerhaus, G J; Visser, M; Ten Kate, F J; de Boer, O J; Tijssen, J G; Bergman, J J; Meijer, S L (Diseases of the esophagus, 2017)
Management of Barrett's esophagus (BE) relies heavily on histopathological assessment of biopsies, associated with significant intra- and interobserver variability. Guidelines recommend biopsy review by an expert in case of dysplasia. Conventional review of biopsies, however, is impractical and does not allow for teleconferencing or annotations. An expert digital review platform might overcome these limitations. We compared diagnostic agreement of digital and conventional microscopy for diagnosing BE ± dysplasia. Sixty BE biopsy glass slides (non-dysplastic BE (NDBE); n = 25, low-grade dysplasia (LGD); n = 20; high-grade dysplasia (HGD); n = 15) were scanned at ×20 magnification. The slides were assessed four times by five expert BE pathologists, all practicing histopathologists (range: 5-30 years), in 2 alternating rounds of digital and conventional microscopy, each in randomized order and sequence of slides. Intraobserver and pairwise interobserver agreement were calculated, using custom weighted Cohen's kappa, adjusted for the maximum possible kappa scores. Split into three categories (NDBE, IND, LGD+HGD), the mean intraobserver agreement was 0.75 and 0.84 for digital and conventional assessment, respectively (p = 0.35). Mean pairwise interobserver agreement was 0.80 for digital and 0.85 for conventional microscopy (p = 0.17). In 47/60 (78%) of digital microscopy reviews a majority vote of ≥3 pathologists was reached before consensus meeting. After group discussion, a majority vote was achieved in all cases (60/60). Diagnostic agreement of digital microscopy is comparable to that of conventional microscopy. These outcomes justify the use of digital slides in a nationwide, web-based BE revision platform in the Netherlands. This will overcome the practical issues associated with conventional histologic review by multiple pathologists.